2020
DOI: 10.1186/s13690-020-00463-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, food insecurity, and depression among females

Abstract: Background Nutritional psychiatry is an emerging field of research and it is currently exploring the impact of nutrition and obesity on brain function and mental illness. Prior studies links between obesity, nutrition and depression among women. However, less is known how food insecurity may moderate that relationship. Methods Data were employed from the Collaborative Psychiatric Epidemiology Surveys (CPES), 2001–2003. Two logistic regression models were Logistic regression was used to determine the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…It revealed greater frequency of them in obese have average and below average level of mental health, while non-obese have more frequency in average and above average level of mental health. This finding is supported in line with previous studies as mental health issues such as anxiety, depression and stress have positive relationship with obesity(AlQahtani et al 2015), obese patient have greater chances for depression(Reynolds et al 2018), mental health of obese people acted as strongest predictor for perceived physical health(Knoesen et al 2010), and obesity was highly associated with depressive disorder especially in women(Ahuja et al 2020).…”
supporting
confidence: 87%
“…It revealed greater frequency of them in obese have average and below average level of mental health, while non-obese have more frequency in average and above average level of mental health. This finding is supported in line with previous studies as mental health issues such as anxiety, depression and stress have positive relationship with obesity(AlQahtani et al 2015), obese patient have greater chances for depression(Reynolds et al 2018), mental health of obese people acted as strongest predictor for perceived physical health(Knoesen et al 2010), and obesity was highly associated with depressive disorder especially in women(Ahuja et al 2020).…”
supporting
confidence: 87%
“…From the gender perspective, CME could more dramatically improve rural women’s adult health than men, especially in mental health. Some studies have shown that women are worse than men on most health indicators [ 46 , 64 ]. Fortunately, the childhood migration of China’s rural population is more favorable to women, promoting health equality at the gender level.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another study ( 22 ) of residential female undergraduates discovered that higher DII was significantly associated with an increased likelihood of stress symptoms (OR = 1.41, 95% CI: 1.12–1.77; P = 0.003) and anxiety symptoms (OR = 1.35, 95% CI: 1.07–1.69; P = 0.01). The relationship between dietary patterns and depression remains significant, and strong epidemiological evidence proposes that poor diet may hurt mental health disorders ( 23 ). However, after adjusting for marriage, education, and family poverty to income ratios, the significance of DII concerning the risk of suicide in older patients decreased significantly.…”
Section: Discussionmentioning
confidence: 99%